Enhancing the spatially distributed total bed material load prediction using correction factor grid for plane bedded mountain river / Amir Nazaruddin - Nazaruddin, Amir (2015)
The sediment transport in river is a dynamic phenomenon which usually estimated based on reach average concept using Total Bed Material Load (TBML) equation. However, due to high heterogeneity of particle size and different morphologies in mountain river channel sediment transport in mountain river cannot be treated similar to its lowland counterpart. As such, the present research was carried out at Sungai Sedim by applying high resolution bed profiling and total load measurement. A total of 36 numbers of sampling cell was prepared within the six meter by six meter study reach. Sediment data was collected fromeach sampling cell while the bed profile was measured at every 0.2 meter increment at each axis for the entire study reach. The measured bed elevation was transformed into Digital Elevation Model (DEM) and further expanded to Triangulated Irregular Network (TIN) model using ArcGIS9.3. Based on geostatistical and cell resolution analysis conducted, Radial Basis Function (RBF) was identified to be the most suitable interpolation method to be used in the study. Similar method also applied to derive the measured total load grid for the study area. TBML equation by Sinnakaudan (2010) was employed to formulate a spatial distribution prediction model to show the spatial discrete variability of the total load using the map algebra functions. Discrepancy Ratio (DR) analysis indicates that the prediction model fails to show the variability in the total load for the study reach. Thus, a Correction Factor Grid (CFG) was introduced. The application of CFG shows a promising DR result of 80.5% and 54.9% for two set of sample tested respectively. Thus, it is recommended that TBML equation should include spatial variability and localized properties in its derivation since the inclusion of spatial variability provides more precise overview towards sediment transport pattern at mountain rivers.